2020
DOI: 10.1523/jneurosci.2148-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine Modulates Cerebellar Granule Cell Spiking by Regulating the Balance of Synaptic Excitation and Inhibition

Abstract: Sensorimotor integration in the cerebellum is essential for refining motor output, and the first stage of this processing occurs in the granule cell layer. Recent evidence suggests that granule cell layer synaptic integration can be contextually modified, although the circuit mechanisms that could mediate such modulation remain largely unknown. Here we investigate the role of ACh in regulating granule cell layer synaptic integration in male rats and mice of both sexes. We find that Golgi cells, interneurons th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…These results suggest that the activity balance between D-GCs and M-GCs could be altered by the situations affecting the overall excitation-inhibition (E-I) balance in the GCL. A recent study reported that acetylcholine regulates the balance of synaptic excitation and inhibition in the GCL and consequently GC excitability [ 48 ]. Anatomical studies showed the presence of cholinergic projections into the cerebellum by the observation of choline acetyltransferase-positive MF-like terminals or thin beaded fibers originating from diverse sources [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the activity balance between D-GCs and M-GCs could be altered by the situations affecting the overall excitation-inhibition (E-I) balance in the GCL. A recent study reported that acetylcholine regulates the balance of synaptic excitation and inhibition in the GCL and consequently GC excitability [ 48 ]. Anatomical studies showed the presence of cholinergic projections into the cerebellum by the observation of choline acetyltransferase-positive MF-like terminals or thin beaded fibers originating from diverse sources [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such measurements have not, however, revealed that consistency of mossy fiber input is translated into consistency of spike timing, which may vary considerably due to intrinsic membrane properties and other inputs. For example, while our experiments are designed to address fast synaptic inhibition provided by GABA A receptors, they do not address the contributions of GABA B receptors 54 , neuromodulators 38, 55 , or cell-intrinsic conductances, such as voltage-activated potassium currents, that can alter the relationship between synaptic input and spiking 39 . We also note that the reliability of inputs may be modality specific 56 , as different mossy fibers can have different strengths and short-term plasticity, and likely have different temporal consistency depending on source.…”
Section: Discussionmentioning
confidence: 99%
“…Because behavior and learning can be context-specific, we suggest that factors regulating granule cell inhibition may provide a powerful basis for enhancing patterns that should be learned or preventing learning in other contexts. In particular, Golgi cells can be bi-directionally modulated by acetylcholine and serotonin 38, 55 . Thus, our measurements suggest that these neuromodulators are likely candidates to enable context specific cerebellar behavior and learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacity of the brain to accommodate information precisely within a limited time window is important for reliable execution of complex sensory and motor behaviors [1,2]. When the cerebellar cortex is injured, the movement loses precision and becomes uncoordinated and incorrectly timed, occurring in both humans [3][4][5] and animals [6,7].…”
Section: Introductionmentioning
confidence: 99%